Feasibility study of personalized peptide vaccination for recurrent ovarian cancer patients. (June 2014) - Kawano, Kouichiro; Tsuda, Naotake; Matsueda, Satoko; Sasada, Tetsuro; Watanabe, Noriko; Ushijima, Kimio; Yamaguchi, Tomohiko; Yokomine, Masato; Itoh, Kyogo; Yamada, Akira; Kamura, Toshiharu
Abstract Context: To develop a personalized peptide vaccine (PPV) for recurrent ovarian cancer patients and evaluate its efficacy from the point of view of overall survival (OS), Phase II study of PPV was performed. Patients and methods: Forty-two patients, 17 with platinum-sensitive and 25 with platinum-resistant recurrent ovarian cancer, were enrolled in this study and received a maximum of four peptides based on HLA-A types and IgG responses to the peptides in pre-vaccination plasma. Results: Expression of 13 of the 15 parental tumor-associated antigens encoding the vaccine peptides, with the two prostate-related antigens being the exceptions, was confirmed in the ovarian cancer tissues. No vaccine-related systemic severe adverse events were observed in any patients. Boosting of cytotoxic T lymphocytes or IgG responses specific for the peptides used for vaccination was observed in 18 or 13 of 42 cases at 6th vaccination, and 19 or 29 of 30 cases at 12th vaccination, respectively. The median survival time (MST) values of the platinum-sensitive- and platinum-resistant recurrent cases were 39.3 and 16.2 months, respectively. The MST of PPV monotherapy or PPV in combination with any chemotherapy during the 1st to 12th vaccination of platinum-sensitive cases was 39.3 or 32.2 months, and that of platinum-resistant cases was 16.8 or 16.1 months, respectively. Importantly, lymphocyte frequency and epitope spreading were significantly prognostic of OS. Discussion and conclusion: Because of the safety and possible prolongation of OS, a clinical trial of PPV without chemotherapy during the 1st to 12th vaccination in recurrent ovarian cancer patients is merited.